Sosialisasi Pentingnya Pemilahan Sampah Organik dan Anorganik Rumah Tangga di Desa Penantian - Djorghi Samudra Triananda; Sela Monika; Cahya Putri Angraini; Muhammad Latif; Baihaqi Baihaqi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Household waste management remains an environmental challenge in Penantian Village, Kelam Tengah District, Kaur Regency. The village has no designated final disposal site (TPA), while community awareness and knowledge of waste segregation remain limited. Organic and inorganic household waste is still mixed and commonly managed by burning or dumping it into the river, potentially causing environmental pollution and reducing community well-being. This community service activity aimed to improve community knowledge and awareness of the importance of separating organic and inorganic waste at the household level. The method used was direct outreach and education with a descriptive approach. The materials included waste classification, the importance of household waste segregation, the impacts of burning and dumping waste into rivers, and simple waste management alternatives. The results showed increased community understanding of waste types and the importance of segregation before disposal or utilization. This activity is expected to encourage household waste segregation habits and support community participation in maintaining a cleaner environment in Penantian Village.